Interfacial and emulsifying properties of amaranth (Amaranthus hypochondriacus) protein isolates under different conditions of pH - Ventureira, Jorge Luis (2011)
Amaranth proteins have adequate amino acid balance for substituting either partly or completely animal proteins in human nutrition. However, they present poor emulsifying properties in basic conditions corresponding to their extraction medium. Consequently their use in acidic conditions could be envisaged to better exploit their potentialities. To better understand their emulsifying properties we have studied their interfacial activities at pHs 2.0 and 8.0 and tried to make the link between 2D and 3D properties. Our results clearly demonstrate the better properties of AI at pH 2.0 than at pH 8 in terms of protein solubility, spreading, adsorption, viscoelastic properties of interfaces and emulsion stability. These results are in relation with the denaturated state of proteins at pH 2.0 where proteins form a harder interfacial film, as compared to pH 8.0. Thus the potential use of amaranth proteins in emulsifying applications should be oriented towards acidic applications.